Livelihood Security of Small Farmers in Jabalpur District of Madhya Pradesh (Indian Journal of Extension Education, 2020)
The research study was conducted in the Shahpura block of district Jabalpur in Madhya Pradesh with 120 small farmers to analyze their livelihood security. It was found from the study that more than sixty percent of the small farmer had a medium level of food security and more than fifty percent of the small farmer were having a medium level of occupational security. It was also observed that 53.33 per cent of the small farmer had a medium level of habitat security, 62.50 per cent of the small farmer were having a medium level of educational security, more than sixty percent of the small farmer had a low level of social security, more than fifty percent of the small farmer in the study area were having a medium level of health security. The majority of the small farmer had a medium level of environmental security. More than sixty percent of the small farmers came in the category of having medium Livelihood security. Habitat security was observed with the highest index value of 0.731 while social security had the lowest index value of 0.256.